(untitled) (Innovaciones Educativas, 2025)
In a global context characterized by profound transformations in educational systems, this article proposes to explore new ways of understanding and exercising educational leadership from a perspective focused on the well-being of the members of the community and that moderates the retention of human talent in schools. Understanding leadership as the social force of pedagogical change, we seek to identify some of the key elements that are absent from the traditional talks about educational improvement. Under the title "Dream, Create, and Care," it invites us to rethink leadership not only as a bureaucratic practice centered on the central figure of "a leader," but as a profoundly human, situated, and ethical action. To dream implies opening space for pedagogical imagination and collective hope, making more just, inclusive, and sustainable possible futures visible. To create alludes to the capacity to design and sustain innovative, resilient, and collaborative school communities, where change is not imposed but co-constructed through dialogue and active participation. Caring, finally, emphasizes the need for an affective and relational view of institutional life, recognizing that the well-being of the actors—especially teachers—is an essential component of any improvement process.